KUALITAS TELUR AYAM ISA BROWN UMUR 18-22 MINGGU PASCA DIVAKSINASI EGG DROP SYNDROME DAN DIBERI RANSUM DALAM JUMLAH YANG BERBEDA - Sumayani, N. K. E.; G. A. M. K. Dewi; G. A. Y. Kencana (Jurnal Peternakan Tropika, 2019)
Egg drop syndrome causes a decrease in the quality and quantity of eggs so it does not benefit farmers. The research was conducted at the Faculty of Animal Science, Bukit Jimbaran Campus, and egg quality tested every week in the Poultry Laboratory of the Faculty of Animal Science, Sudirman Campus, Denpasar, which lasted for 5 weeks. The study sample was used by Isa Brown laying hens on an average age of 18 weeks. The study design used a completely randomized design (CRD) consisting of 3 treatments and 5 replications. Each replication consisted of 3 laying 1 control hens of Isa Brown so that the total chickens used were 45 tails.The treatment of this study was R1:Chicken Isa Brown without a vaccine candidate and given a commercial ration of 80 g/head/day, R2:Chicken with candidates for the EDS vaccine and given a commercial ration of 80 g/head/day R3:Chicken with candidates vaccine EDS and given 84 g/head/day of commercial ration. The variables observed were egg weight, egg index, shell weight, shell thickness, egg yolk color, pH and, haugh unit. The results showed that treatment R2 and R3 (P<0,05) were able to increase egg weight, eggshell weight, eggshell thickness, egg yolk color and haugh unit compared to treatment R0 but there was a decrease in egg shape index, egg pH on R2 treatment. Based on the results of the study it can be concluded that the quality and quantity of R3 eggs is higher than the treatment of R2 in chiken egss Isa Brown aged 18-22 week. Keywords : Isa Brown, quality of eggs, rations, vaccine candidates, egg drop syndrome